A Rare Case with 49,XXXXY Syndrome - M Alijanpour,; A Hadipoor; M Taghavi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2012)
BACKGROUND AND OBJECTIVE: Chromosomal abnormalities are one of the causes of sexual ambiguity and in male genders the most common causes of genital ambiguity in chromosomal abnormalities’ category is Klinefelter syndrome and its rare 49,XXXXY syndrome variant. The main findings in these patients are facial and skeletal malformations, congenital heart defects, hypogonadism, and mental retardation. Determination of infant gender with sexual ambiguity at the time is very important and with timely diagnosis we can improve growth and development and treat associated anomalies.CASE: We report an 11 month old infant that initially was managed by pediatric cardiologist for congenital heart disease and referred to endocrinology clinic due to failure to thrive, facial malformations and ambiguous genitalia. The patient had a history of hospitalization for pneumonia in the PICU at the age of 10 months and improved after the treatment. After clinical examination, hormonal studies and karyotype, Klinefelter syndrome and its 49,XXXXY syndrome variant was diagnosed after 2 months. Then testosterone ampule was injected and orchiopexy surgery was performed. In follow-up, the patient was able to sit at the age of 18 months. CONCLUSION: In patients referred with ambiguous genitalia, mental retardation, facial anomalies and developmental disorders, 49,XXXXY syndrome and other similar syndromes must be considered and simultaneously they should be managed for cardiac problems, genital ambiguity, growth and development.